PENGARUH SOLVABILITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT LIPPO CIKARANG TBK PERIODE 2013-2023 - Siti Saadiyah; Sairin (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of Solvability (Debt to Equity Ratio) and profitability (Net Profit Margin) on company value (Price to Book Value) at PT Lippo Cikarang Tbk for the period 2013-2023. The research method used is descriptive with a quantitative approach. The data utilized is secondary data in the form of annual financial statements from PT Lippo Cikarang Tbk for the period 2013-2023, which is listed on the Indonesia Stock Exchange (IDX). The results of this study indicate that partially, the Solvability (Debt to Equity Ratio) has a significant effect on the company's value (Price to Book Value), where the calculated T value is greater than the T table value, specifically 2.537> 2.306, with a significance level of 0.035, which is less than 0.05 (0.035 < 0.05). Meanwhile, partially, Profitability (Net Profit Margin) does not have a significant effect on the company's value (Price to Book Value), as the calculated T value is less than the T table value, specifically 0.541 < 2.306, with a significance level of 0.603, which is greater than 0.05 (0.603 > 0.05). Furthermore, simultaneously, Solvability (DER) and Profitability (NPM) do not have a significant effect on the company's value (PBV), as the calculated F value is less than the F table value, specifically 3.354 < 4.459, and the significance value is 0.088, which is greater than 0.05 (0.088 > 0.05).